ILLOCUTIONARY OF COMPLAINING ASSERTIVES IN MEME - Syifana Annisa Putri; Juanda Juanda (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
This article is going to be about illocutionary act in memes during covid-19 pandemic. Speech acts consist of locutionary act, illocutionary act, and perlocutionary act. Locutionary act is an act merely to say something. Whilst illocutionary act, the speakers produce a function in saying something. In other words, the speakers have a certain purpose in saying something, namely requesting, offering, ordering, commanding, and so forth. Meanwhile, perlocutionary act is an utterance uttered by the speakers has a certain function and meaning to give certain effects to the hearer, such as convincing, persuading, obstructing, even misleading. Assertives illocutionary act contains a function such as stating, concluding, boasting, and complaining. This discussion’s main focus is on assertive illocutionary act in complaining. The method used in this article is descriptive method. The source was taken from https://9gag.com/gag/axMnXqp. The result obtained consist hopes for Covid-19 to end soon because it has impacted the economic field and others in so many ways. The impact of this article is for everyone to be able to deal with the conditions they’re facing at the moment and to be prepared with the unexpected conditions at the same time. Key words: Illocutionary, Pandemic, Meme